Lectotypification and a new synonym for Gymnanthes klotzschiana (Euphorbiaceae) - Oliveira, Luciana Dos Santos Dias De; Melo, André Laurênio De; Silva, Marcos José Da; Sales, Margareth Ferreira De (Phytotaxa, 2013)
Gymnanthes klotzschiana is one of the most problematic species of its genus, not only from a morphological point of view, but also concerning its nomenclature. From among its syntypes, we propose herein the lectotypification of the name. Additionally, studies of herbarium material of Actinostemon unciformis and G. klotzschiana, including type and historical collections, have shown that they are conspecific. The second name has priority over the first. These considerations are part of an ongoing review of Gymnanthes.